Noun Incorporation in Bahasa Indonesia - Muhammad Kiki Wardana; Mulyadi (Britain International for Academic Research (BIAR) Publisher, 2022)
Indonesian has always been ignored as a source of Noun Incorporation. This happens because of the agglutinative nature of Indonesian. This means that many words in Indonesian are formed by combining several morphemes. Even so, it is possible that in fact a lot of Noun Incorporation (IN) processes occur in Indonesian. This research uses Mithun and Rosen's approach in searching for Incorporation of Nouns in Indonesian. The results of this study reveal that the incorporation of nouns in Indonesian even though they are not productive, still occurs at level I and II. The incorporation of nouns of Mithun's ideas and also surprisingly (needs further investigation) occurs in two types of Rosen's ideas, namely Compounding Nominal Incorporation and Nominal Incorporation. Classifier. This research also reveals that many incorporation of nouns in Indonesian are idiomatic and according to (Mithun, 1986) this is common in several languages.